2021
DOI: 10.1002/smll.202103169
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Halide Perovskite Films by Vapor Anion Exchange for Spectrally Stable Blue Stimulated Emission

Abstract: All-inorganic perovskites such as CsPbX 3 have attracted huge attention because of its superior stability. [6] So far, perovskite nanowires, microplates, and films have been used to realize lasing or amplified spontaneous emission (ASE). Both lasing and ASE are a kind of light amplification through stimulated emission when there is an inverted population between two energy states. [7] Stimulated emission is that an incident single photon stimulates other recombination and creates an additional photon which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…This number is consistent with the reported amplified spontaneous emission thresholds for blue-emitting CdSe (50 ÎŒJ/cm 2 ), or CdS and CdS/ZnS NPLs (50–250 ÎŒJ/cm 2 ), and is significantly lower than typical thresholds for blue quantum dots (∌1 mJ/cm 2 ) ,, unless the latter are carefully engineered to introduce a smooth confinement potential, which reduces the threshold to 60 ÎŒJ/cm 2 . Moreover, our values are comparable to typical thresholds (63–190 ÎŒJ/cm 2 ) reported for blue-emitting perovskite nanostructures. − …”
supporting
confidence: 92%
See 1 more Smart Citation
“…This number is consistent with the reported amplified spontaneous emission thresholds for blue-emitting CdSe (50 ÎŒJ/cm 2 ), or CdS and CdS/ZnS NPLs (50–250 ÎŒJ/cm 2 ), and is significantly lower than typical thresholds for blue quantum dots (∌1 mJ/cm 2 ) ,, unless the latter are carefully engineered to introduce a smooth confinement potential, which reduces the threshold to 60 ÎŒJ/cm 2 . Moreover, our values are comparable to typical thresholds (63–190 ÎŒJ/cm 2 ) reported for blue-emitting perovskite nanostructures. − …”
supporting
confidence: 92%
“…33 Moreover, Lu et al reported a value of g net = 129 cm −1 using quasi-2D mixed-Br/Cl Cs-based perovskite films fabricated via a vapor anion exchange method. 47 Since these modal gain values are well below our material gain coefficients, we can conclude that our g i present state-of-the-art values for solution-processed blue-emitting nanomaterials.…”
mentioning
confidence: 55%
“…It is usually necessary to ensure that the source is volatile or volatile under certain conditions, ions volatilized into the vapor phase do not introduce other impurities, and the volatilized vapor does not cause corrosion and damage to the film surface. In view of this, common vapor-phase sources include precursor vapors, volatile HX (X = Cl, Br, I), diphenylphosphinyl chloride (DPPOCl), 60 TiCl 4 , 61 and so on. Sun et al 62 proposed an ingeniously designed temperature bridge to construct the compositional gradient.…”
Section: Compositional Gradient Engineeringmentioning
confidence: 99%
“…They achieved tunable emission and ASE from green region to blue region at room temperature based on those polycrystalline films. [17] However, compared with CsPbX 3 single-crystal thin films, CsPbX 3 polycrystalline film exhibit higher threshold and lower optical gain due to their structural inhomogeneities, rough surface, unavoidable grain boundaries, and higher trap densities. In contrast, perovskite single-crystal thin films (SCTFs) have a flat surface, lower trap densities and fewer defects, which is beneficial to enhance laser device performance and stabilities.…”
Section: Introductionmentioning
confidence: 99%